Feasibility Study of Early Blood Pressure Management in Extremely Preterm Infants - Batton, Beau J. (2012)
OBJECTIVE: To assess the feasibility of a randomized placebo controlled trial (RCT) of blood pressure (BP) management for extremely preterm infants. STUDY DESIGN: This was a prospective pilot RCT of infants 23(0/7) – 26(6/7) weeks gestation who had protocol-defined low BP in the first 24 postnatal hours. Enrolled infants were administered a study infusion (dopamine or placebo) and a study syringe medication (hydrocortisone or placebo). RESULTS: Of the 366 infants screened, 119 (33%) had low BP, 58 (16%) met all entry criteria, and 10 (3%) were enrolled. 161 (44%) infants were ineligible because they received early indomethacin. Only 17% of eligible infants were enrolled. Problems with consent included insufficient time, parent unavailability, and physician unwillingness to enroll critically ill infants. Two infants were withdrawn from the study due to the potential risk of intestinal perforation with simultaneous administration of hydrocortisone and indomethacin. CONCLUSIONS: This pilot RCT was not feasible due to low eligibility and consent rates. An RCT of BP management for extremely preterm infants may require a waiver of consent for research in emergency care. The frequent use of early indomethacin and the associated risk of intestinal perforation when used with hydrocortisone may limit future investigations to only inotropic medications.